Jurnal Review : Daging Kambing/Domba Bukan Faktor Penyebab Tekanan Darah Tinggi (Hipertensi): Journal Review: Goat and Lamb Meat Is Not a Causative Factor of High Blood Pressure (Hypertension) - Aminurrahman; Ine Karni; Rezki Amalyadi; Zaid Al Gifari; I Gede Nano Septian; Musanip (Universitas Muhammadiyah Palu, 2025)
Hypertension is a global health issue that often goes unnoticed due to its lack of symptoms and poses a risk of serious complications such as heart disease and stroke. One food frequently associated with elevated blood pressure is goat meat. This article aims to review various research findings regarding the relationship between goat meat consumption and the risk of hypertension. The method used is a literature review of 20 scientific articles published between 2001 and 2022, obtained from databases such as Google Scholar and PubMed. The findings indicate that consuming goat meat in moderation does not cause hypertension, primarily due to its lower saturated fat content compared to beef and chicken. Hypertension is more influenced by genetic factors, high-sodium diets, and unhealthy lifestyles. Excessive salt used in the preparation of goat meat dishes may trigger high blood pressure, particularly in individuals with impaired kidney function. From an Islamic perspective, moderate meat consumption was also exemplified by the Prophet Muhammad (peace be upon him) and his companions. Therefore, goat meat can serve as a nutritious food source if consumed wisely in appropriate portions and frequency.